Trends in international mathematics and science study (TIMSS) as a measurement for students’ mathematics assessment development - Andi Mawaddah Hamzah (Balai Diklat Keagamaan Ambon, 2023)
The Trend in International Mathematics and Science Study (TIMSS) is a comprehensive study that aims to look at the mapping of the education system through evaluation in the fields of mathematics and science. Indonesia is one of the countries involved in this periodic evaluation system every four years. Considering Indonesia's position which is still relatively low (ranked 35th out of 46 countries) in the 2015 TIMSS, the Indonesian government then decided not to become one of the TIMSS evaluation objects in 2019 while formulating its evaluation system. This article aims to examine the TIMSS 2023 framework which is used as a benchmark in the development of a national evaluation/assessment system in Indonesia. Furthermore, this article will contain the process of developing TIMSS standard questions. The method used is a Systematic Literature Review (SLR). The main literature in the preparation of this article is the TIMSS 2023 Assessment Frameworks. The other supporting literature comes from the results of research on related topics. In addition to the results of the systematic literature review (SLR) conducted, the findings of this research include the questions developed by the standards set by TIMSS 2023. The questions developed are focused on the field of mathematics for grade 4, specifically in the domain of Numbers.